Learning History Using Augmented Reality - Nur Ain Najihah Ibharim; Siti Zalifah Ramli; Siti Aishah Zahari; Nur Amalia Atikah Edyanto; Muhammad Asyraf Abdullah Zawawi (International Journal of Multimedia and Recent Innovation, 2021)
Subject of history is one of the subject that must be passed in the SPM examination. Subjet of history is very important in our life as a guides and teaches us in how to progress and advance not making the same mistakes. We also must have deep knowledge about history of homeland so we can appreciate them and also make them all our idols. However, learning about history of homeland warrior can be challenging, especially for student who think that learning about history is boring and some student are less aware of the importance of studying history. For help teacher to teach and also attract student in learn about history, we are try to use Augmented Reality for make learning session fun. The research aims to design an application for learning history of homeland using Augmented Reality.